1999
DOI: 10.1053/jvet.1999.0038
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Four Methods of Progressive Venous Attenuation in Dogs

Abstract: Both ameroid constrictor implantation and cellophane banding show promise for progressive attenuation of single extrahepatic portosystemic shunts in dogs. Because rapid occlusion was seen with ameroid constrictors, however, cellophane banding maybe a safer technique in animals with increased hepatic vascular resistance. Further evaluation of both treatments in clinical cases is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
103
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(109 citation statements)
references
References 24 publications
5
103
0
1
Order By: Relevance
“…It has been suggested that PSS occlusion over a 6-week period would be unlikely to cause portal hypertension, based on previous documentation of successful complete ligation of PSS at a second laparotomy within one month after the initial partial ligation. [11][12][13] To this end, investigators have attempted gradual occlusion of PSS by a variety of methods, including cellophane banding, 14,15 intravascular coils, 16 and partial ligation with silk. 17,18 Most recently, ameroid constrictors (AC) have been recommended as an effective device for progressive occlusion of PSS and have gained widespread clinical use in North America.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that PSS occlusion over a 6-week period would be unlikely to cause portal hypertension, based on previous documentation of successful complete ligation of PSS at a second laparotomy within one month after the initial partial ligation. [11][12][13] To this end, investigators have attempted gradual occlusion of PSS by a variety of methods, including cellophane banding, 14,15 intravascular coils, 16 and partial ligation with silk. 17,18 Most recently, ameroid constrictors (AC) have been recommended as an effective device for progressive occlusion of PSS and have gained widespread clinical use in North America.…”
mentioning
confidence: 99%
“…8,19,20 Unfortunately, none of these methods of vascular occlusion has been reported to produce reliable complete occlusion over a 6-week period. 11,19 In addition, in two recent studies applying AC to single extrahepatic PSS in dogs and cats, 17% of the animals (17% 19 , 17.5% 21 ) were found to have developed multiple extrahepatic shunts at long term follow-up. 19,21 Another study of clinical results after AC in 24 cats with single extrahepatic PSS reported that 8 of 14 cats (57%) had persistent shunting 8-10 weeks after surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study from 1999, the femoral vein was dissected from the surrounding connective tissue without any tissue attachment and fibrosis could be easily stimulated by the cellophane resulting in vessel occlusion (Youmans and Hunt 1999). However, in the case reported here, the shunt vessel was inserted into the central tendon fibres and it was not possible to dissect the shunt without the tendon fibres.…”
Section: Discussionmentioning
confidence: 93%
“…When portal blood bypasses the hepatic sinusoids, the liver is deprived of hepatotrophic substances including insulin and glucagon, and the systemic circulation and brain are exposed to nonmetabolised intestinal toxins (Youmans and Hunt 1999). Medical management may control hepatic encephalopathy in the short term; however, a progressive deterioration in liver function occurs until shunt occlusion (Worley and Holt 2008).…”
Section: Discussionmentioning
confidence: 99%